Pequeños mamíferos del Plioceno del sitio de Udunga del área de Transbaikalia - Erbajeva, Margarita; Alexeeva, Nadezhda; Khenzykhenova, Fedora (Coloquios de Paleontología, 2003)
In the Transbaikal area, the oldest known fauna is from Udunga site of the early Late Pliocene which was attributed to the Udunginian Faunistic Complex. It is characterized by its peculiar mammal fauna, including some Ruscinian forms previously unknown in this region, and several new large and small mammalian taxa found in the Transbaikal area for the first time. Among small mammals, a new cricetid taxon (Gromovia daamsi n. gen., n. sp.) is recognized and described here. The analysis of the fauna shows the predominance of forest inhabitants